Adverse Outcomes due to Aggressive Fluid Resuscitation in Children: A Prospective Observational Study - Muttath, Anand; Annayappa Venkatesh, Lalitha; Jose, Joe; Vasudevan, Anil; Ghosh, Santu (Journal of Pediatric Intensive Care, 2019)
Fluid management has a major impact on the duration, severity, and outcome of critically ill children. The aim of this study was to examine the relationship between cumulative fluid overload (CFO) with mortality and morbidity in critically ill children. This was a prospective observational study wherein children (1 month–16 years) who were critically ill (with shock requiring inotropes and/or mechanically ventilated) were enrolled. CFO was defined as the sum of daily fluid balances. Daily fluid balance was calculated as a difference between fluid intake (oral and intravenous) and output (urine output, discharge from nasogastric tube) in 24 hours. Percentage of fluid overload (FO) (PFO) was calculated as the ratio of CFO with weight at admission in kilogram. The CFO and PFO at 24, 48, 72 hours and at 7 days or end of PICU stay were calculated. A total of 291 children (244 survivors and 47 non-survivors; 47% males) were included in the final analysis. A higher mortality was observed in children with higher PFO (>20% FO: 45.8% mortality vs. 14.5% < 10% FO, p < 0.01) and CFO (10.97 ± 6.4 mL/kg in survivors vs. 13.95 ± 9.6 mL/kg in non-survivors; p = 0.022) at 72 hours. A 1% increase in fluid overload was associated with 6% and 4% increase in mortality at 72 hours and 7 days, respectively. Similarly, the impact of every 1% increase in fluid overload on both ventilation (yes/no) and acute kidney injury (AKI; yes/no) were found to be significant for both parameters at 72 hours, but only AKI had significant correlation on seventh day. In the multivariate stepwise Cox's proportional hazard model for PICU stay and hospital stay, 3% (p < 0.05) and 2% (p > 0.05) increase were found for every 1% increase in fluid overload, respectively. Oxygenation index is also associated with fluid overload with the adjusted model estimated 0.27 units (95% confidence interval: 0.18–0.36) increase per 1% increase in fluid overload. FO was associated with increased mortality and morbidity in critically ill children.
Keywords: critically ill; intensive care units; pediatric; critical care; fluid; therapy